The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s10554-014-0543-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of morphologic findings obtained by optical coherence tomography in acute coronary syndrome caused by vasospasm and chronic stable variant angina

Abstract: This study used optical coherence tomography (OCT) to evaluate morphologic changes in vasospastic lesions, which can cause acute coronary syndrome (ACS) or chronic stable VA. Thirty-nine patients (52.4 ± 9.0 years, 33 males) with vasospasm-induced ACS who presented with chest pain and displayed transient ST segment elevation on electrocardiography were included in the ACS group. Forty-one patients (49.3 ± 7.7 years, 33 males) who presented with chronic stable variant angina were included in the VA group. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Moreover, the OCT data supported the CAS findings; this indicates that focal CS was associated with a thicker intima-media layer with a lipid-rich plaque. Our findings are consistent with our previous IVUS report [11] or the findings of other previous reports [7,[28][29][30]. Focal CS is caused by local hyperreactivity to a generalized constrictor stimulus in mild atherosclerosis [25].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the OCT data supported the CAS findings; this indicates that focal CS was associated with a thicker intima-media layer with a lipid-rich plaque. Our findings are consistent with our previous IVUS report [11] or the findings of other previous reports [7,[28][29][30]. Focal CS is caused by local hyperreactivity to a generalized constrictor stimulus in mild atherosclerosis [25].…”
Section: Discussionsupporting
confidence: 93%
“…[ 26 , 27 ] Recently, some investigators found intimal erosion and lumen irregularities on optical coherence tomography in patients with CV and acute coronary syndromes. [ 28 , 29 ] Therefore, another form of atherosclerosis has been suggested in spastic arteries. [ 30 ] The structural changes in the epicardial coronary arteries can be visualized using intracoronary imaging techniques; however, microvascular changes can be assessed indirectly such as with hyperemic microvascular resistance.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that coronary a peripheral thrombus or the plaque composition causes occlusion, myocardial microcirculation disorders, cardiac syncope, and ischemia-reperfusion injury (e.g., freedom injury, vascular endothelial tissue injury, inflammatory cell infiltration, and myocardial edema) [ 23 , 24 ]. With the development of coronary and myocardial perfusion and coronary morphology evaluation tools, an increasing number of studies show that micro-thrombi (15 ~ 100μm) caused by unstable plaque ruptures in the intervention process play a very important role in the mechanism of myocardial reperfusion [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%